Écrire l’histoire du Québec pour les touristes - Serge Jaumain (IdeAs)
Printed tourist guides influence the geographical, artistic, cultural, social, political and historical knowledge of millions of visitors who visit Quebec each year. In a few pages, they offer an introduction to a new universe and thus contribute to the construction of collective representations. However most of the historians have ignored their impact. This text presents the first results of a study of Quebec's historical presentations in some seventy tourist guides published in French or English between 1963 and 2016. After examining the way in which these texts are constructed, the study shows that during fifty years there was little change in the discourse, except on two points: indigenous people and the national question. The presentation is intended to be increasingly attentive to the socio-economic situation of the indigenous. Their place in the historical narrative is gradually being revalued. The national question is the central element of many historical introductions, reflecting travellers' concerns about Quebec's autonomist claim. It is especially one of the few places where some guides move away from their traditional neutrality to formulate some judgments about the autonomist movement or, more generally, about relations between Anglophones and Francophones.